Search for electroweak production of charginos and neutralinos at ?s=13 Tev in final states containing hadronic decays of WW, WZ, or WH and missing transverse momentum - Tumasyan, A.; Adam, W.; Andrejkovic, J. W.; Bergauer, T.; Chatterjee, S.; Damanakis, K.; Dragicevic, M. (Elsevier, 2023)
This Letter presents a search for direct production of charginos and neutralinos via electroweak interactions. The results are based on data from proton-proton collisions at a center-of-mass energy of 13 TeV collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 137 fb-1. The search considers final states with large missing transverse momentum and pairs of hadronically decaying bosons WW, WZ, and WH, where H is the Higgs boson. These bosons are identified using novel algorithms. No significant excess of events is observed relative to the expectations from the standard model. Limits at the 95% confidence level are placed on the cross section for production of mass-degenerate wino-like supersymmetric particles & chi;?& PLUSMN; 1 and & chi;?02, and mass-degenerate higgsino-like supersymmetric particles & chi;?& PLUSMN;1,& chi;?02, and & chi;?03. In the limit of a nearly-massless lightest supersymmetric particle & chi;?01, wino-like particles with masses up to 870 and 960 GeV are excluded in the cases of & chi;?02 & RARR; Z & chi;?01 and & chi;?02 & RARR; H & chi;?01, respectively, and higgsino-like particles are excluded between 300 and 650 GeV. & COPY; 2022 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons .org /licenses /by /4 .0/). Funded by SCOAP3.
Keywords: CMS; Gaugino; Electroweakino; Supersymmetry